SELECTION AND EVALUATION SUPPLIER BY CONTRACTOR: CASE STUDY IN INDONESIA - Andi Theo Haryanto; Paul Nugraha; I Gede Agus Widyadana (Dimensi Utama Teknik Sipil, 2019)
This research will discuss about contractors with concrete suppliers and formwork suppliers. The research is conducted to look for ranking criteria and sub-criteria used by contractors to selecting and evaluating concrete and formwork suppliers. The criteria and sub-criteria are refer to Ho et al., (2007) and three new sub-criteria are added, which are a guarantee, lowest price guarantee, and payment term. The contractor classification is divided into four namely general classification, NPK classification consisting of non-classification; individual; small business, medium business classification, and big business classification. Ranking for criteria and sub-criteria are sought based on the mean value for each classification material both in the context of selection and evaluation. After finding the ranking, it is sought whether there is a difference of importance between the NPK classification, middle, and large of the priority sub-criteria in general classification using the Kruskal Wallis test.